ANALYSIS OF MATHEMATICS PROBLEM SOLVING ABILITY IN SOLVING LINEAR EQUATIONS OF ONE VARIABLES IN CLASS VII STUDENTS OF SMP NEGERI 1 SIDUAORI IN ACADEMIC YEAR 2022/2023 - Aprianus Zebua; Ayukasih Soromi (Afore : Jurnal Pendidikan Matematika, 2023)
This study aims to describe the ability to solve students' mathematical problems in solving one-variable linear equations. This research uses a qualitative type of research with a descriptive approach. The informants of this study were class VII-A students of SMP Negeri 1 Siduaori, totaling 22 students. Data analysis with Data collection steps, data reduction, data presentation and conclusion drawing. The research instruments used are problem-solving ability tests and interviews. The research findings show that: out of 22 students, there are 4 students who have very good category math problem solving skills, 2 students have good category math problem solving skills, 3 students have sufficient category math problem solving skills, 7 students have less category math problem solving ability, 6 students have less category math problem solving ability. Thus, from these data, it can be concluded that students' mathematical problem-solving ability in solving one-variable linear equation problems is in the less category with a percentage of 31.8%. Through this research, researchers suggest that teachers create a more pleasant mathematics learning atmosphere and provide habituation to students in solving mathematical problems using the correct procedures or steps to solve them.